Hacking for dummies - Beaver, Kevin (John Wiley & Sons, Inc., 2013)
Until you can think like a bad guy and recognize the vulnerabilities in your system, you can't build an effective plan to keep your information secure. The book helps you stay on top of the security game!
Includes bibliographical references and index
Keywords: Computer security; Computer networks -- Security measures; Hackers; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Pirates informatiques; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures